The Effect of Liquidity, Profitability, and Capital Structure on Firm Value In The Metal and Mineral Industry Sub-Sector Listed On The Indonesia Stock Exchange (IDX) For The 2019-2024 Period - Nora Pirasti; Pristin Prima Sari; Johannes Maysan Damanik (Indonesian Journal Publisher, 2026)
Firm value is an important indicator that reflects a company’s financial performance and market perception, in the metal and mineral industry, which frequently experiences fluctuations in financial conditions and investment decisions. Previous studies have shown inconsistent findings regarding the influence of liquidity, profitability, and capital structure on firm value, highlighting the need for further research. Therefore, this study aims to examine the effect of liquidity, profitability, and capital structure on firm value in the metal and mineral industry sub-sector listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2024. This study employed a quantitative approach using secondary data obtained from the annual financial reports of each company. A purposive sampling technique was used to select 15 companies, resulting in 90 observation data points. Data analysis was conducted using multiple linear regression with SPSS. The results indicate that profitability and liquidity have a positive effect on firm value, while capital structure has a negative effect on firm value. Simultaneously, all variables significantly affect firm value. the coefficient of determination results indicate that liquidity, profitability, and capital structure explain 99,7% of the variationin firm value. In conclusion, liquidity and profitability play a more important role in increasing firm value compared to capital structure in companies within the metal and mineral industry sub-sector.